NiO Supported on Porous Carbon From Merbau Wood: Synthesis and Characterization. Issue 1 (1st March 2022) - Santi, D; Triyono,; Trisunaryanti, W; Falah, I I
Abstract: Nickel oxide catalyst supported on porous carbon (NiO/C), the materials support were synthesized from Merbau wood. The metals were loaded onto the carbon by the wet impregnation method. After drying and calcination, NiO/C was obtained. The prepared catalyst was evaluated for the hydrocracking of pyrolyzed α-cellulose. The catalyst was characterized by XRD, SEM-EDX, FT IR, SAA, and acidity test by NH3 base vapor adsorption determined gravimetrically and by FT IR. The XRD results showed that the carbonaceous of materials support were amorphous materials that characteristic for mesopore carbon. The impregnation of nickel into carbon results in difraktogram peaks that correspond to the presence of NiO, which was confirmed by EDX. The SEM image showed that the morphology of the catalyst samples was a honeycomb-like structure. The acidity test showed that the total acid amount of NiO/C samples was 3.05 mol/g, and the FT IR spectra indicated that there were Brönsted and Lewis acid sites on NiO/C catalyst. The SAA results showed that the specific surface area, total pore volume, and average pore diameter of the NiO/C catalyst were 520.41 m 2 /g, 0.27 cm 3 /g, and 2.083 nm, respectively.